(untitled) - Kerouac, Jack (New York, N.Y., 1991)
On The Road, the most famous of Jack Kerouac's works, is not only the soul of the Beat movement and literature, but one of the most important novels of the century. Like nearly all of Kerouac's writing, On The Road is thinly fictionalized autobiography, filled with a cast made of Kerouac's real life friends, lovers, and fellow travelers. Narrated by Sal Paradise, one of Kerouac's alter-egos, On the Road is a cross-country bohemian odyssey that not only influenced writing in the years since its 1957 publication but penetrated into the deepest levels of American thought and culture.
Keywords: Beat generation,Thế hệ Beat; Fiction,Tiểu thuyết